Oakleaf: an S locus‐linked mutation of Primula vulgaris that affects leaf and flower development. Issue 1 (9th April 2015) - Cocker, Jonathan M.; Webster, Margaret A.; Li, Jinhong; Wright, Jonathan; Kaithakottil, Gemy; Swarbreck, David; Gilmartin, Philip M.
Summary: In Primula vulgaris outcrossing is promoted through reciprocal herkogamy with insect‐mediated cross‐pollination between pin and thrum form flowers. Development of heteromorphic flowers is coordinated by genes at the S locus. To underpin construction of a genetic map facilitating isolation of these S locus genes, we have characterised Oakleaf, a novel S locus‐linked mutant phenotype. We combine phenotypic observation of flower and leaf development, with classical genetic analysis and next‐generation sequencing to address the molecular basis of Oakleaf . Oakleaf is a dominant mutation that affects both leaf and flower development; plants produce distinctive lobed leaves, with occasional ectopic meristems on the veins. This phenotype is reminiscent of overexpression of Class I KNOX‐ homeodomain transcription factors. We describe the structure and expression of all eight P. vulgaris PvKNOX genes in both wild‐type and Oakleaf plants, and present comparative transcriptome analysis of leaves and flowers from Oakleaf and wild‐type plants. Oakleaf provides a new phenotypic marker for genetic analysis of the Primula S locus. We show that none of the Class I PvKNOX genes are strongly upregulated in Oakleaf leaves and flowers, and identify cohorts of 507 upregulated and 314 downregulated genes in the Oakleaf mutant.